1959
DOI: 10.1172/jci103922
|View full text |Cite
|
Sign up to set email alerts
|

Normal Concentrations of Some Trace Metals in Human Urine: Changes Produced by Ethylenediaminetetraacetate *

Abstract: Interest in the biologic role of trace elements prompted an investigation of their renal excretion. Preliminary qualitative analysis revealed that except for cobalt the entire first transition series of metals, namely, titanium, vanadium, chromium, manganese, iron, nickel and copper, were detectable in most human urines. In addition the heavier transition metals, molybdenum and silver, as well as the related metals, zinc, cadmium, tin and lead, were ordinarily present. A method was evolved by which the urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
2

Year Published

1964
1964
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(27 citation statements)
references
References 10 publications
5
20
0
2
Order By: Relevance
“…The 24 h excretion of Na, K, Ca, Mg is well documented and our values are in the same range as those reported, for example, by Staessen et al (1983). The increased urinary elimination of Pb, Mn and Zn after EDTA Ca Na2 infusion is well-documented (Perry & Perry, 1959). In addition, we have now shown that the elimination of Fe and Al is also increased.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The 24 h excretion of Na, K, Ca, Mg is well documented and our values are in the same range as those reported, for example, by Staessen et al (1983). The increased urinary elimination of Pb, Mn and Zn after EDTA Ca Na2 infusion is well-documented (Perry & Perry, 1959). In addition, we have now shown that the elimination of Fe and Al is also increased.…”
Section: Discussionsupporting
confidence: 91%
“…(1986) (10 pg 24 h-1). The high mean concentration of 120 ,ug 1-1 obtained in normal Americans (Perry & Perry, 1959) can be explained by the insufficient sensitivity of the spectrographic method used at that time.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Urine silver levels in an unexposed group are reported to average 1.61 ug/liter with a standard error of the me~n of 0.15 (9). We have adopted an upper limit of normal for unexposed groups as the mean plus two standard errors, or 1.91 ug/l.…”
Section: B Medicalmentioning
confidence: 99%
“…Which metal(s) and which biological constituents are actuaIIy involved, however, is an open question. AIthough the Ca-ehelates lead to a marked zincuria, whereas the exeretion of other trace metals is infl.uenced, if at aII, to a lesser degree (Bohne et al, 1967a;Candura et al, 1960;MilIar et al, 1954;Perry and Perry, 1959;Spencer and Rosoff, 1966;Tarui, 1960;Truhaut et al, 1966), the pathogenetic relevance of these findings, however, is not yet fuIIy understood. Our experimental contribution is eoneerned with same quantitative aspects of the interaction between chelating agents and endogenaus Zn.…”
Section: Institut Für Strahlenbiologiementioning
confidence: 99%